2018
DOI: 10.1002/ijgo.12450
|View full text |Cite
|
Sign up to set email alerts
|

Economic consequences of over‐diagnosis of threatened preterm labor

Abstract: Reductions in inappropriate admissions from applying cervical length-based management protocol could reduce healthcare costs without increasing the incidence of premature delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…In one study, cortisol and α-amylase levels were evaluated in saliva samples from 166 women diagnosed with TPL. The mean cortisol level of the PL group was 3.4 times higher and the α-amylase level was 1.6 times higher than those of the control group, indicating that high cortisol may be an important predictor in the diagnosis of TPL (Coloma et al, 2018). Therefore, RFNC is thought to be effective in reducing cortisol levels by decreasing stress in women.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…In one study, cortisol and α-amylase levels were evaluated in saliva samples from 166 women diagnosed with TPL. The mean cortisol level of the PL group was 3.4 times higher and the α-amylase level was 1.6 times higher than those of the control group, indicating that high cortisol may be an important predictor in the diagnosis of TPL (Coloma et al, 2018). Therefore, RFNC is thought to be effective in reducing cortisol levels by decreasing stress in women.…”
Section: Discussionmentioning
confidence: 86%
“…The level of cortisol in the intervention group was lower than that in the control group. There exists a significant relationship between the cortisol level during pregnancy and TPL (Coloma et al, 2018; Diego et al, 2009; Karakash et al, 2016). In one study, cortisol and α-amylase levels were evaluated in saliva samples from 166 women diagnosed with TPL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microbiological studies into sPB show that intrauterine infections, such as chorioamnionitis, account for about 25%–40% of sPBs, while disturbances of the vaginal microbiome (leading to bacterial vaginosis) and urinary tract infection (UTI), affecting 8% of all pregnant women, are known risk factors for PB ( 2 , 6 , 29 , 30 ). In our study, 36% of the women could be identified with chorioamnionitis and 9% with UTI based on VOCs (respectively, AUC 0.72, sensitivity 0.80 and specificity 0.60), which is in line with the literature ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the earlier the PB, the higher the associated neonatal risks, with 95% of PB occurring after 28 weeks of GA ( 2 , 3 ). The lack of identification of the exact mechanisms leading to sPB hampers the development of accurate prediction and prevention, resulting in increasing health related costs due to unnecessary hospital admittance and treatment ( 4 6 ). Maternal corticosteroids are used as antenatal treatment for women at risk for preterm delivery between 24 + 0 to 33 + 6 weeks of gestation and help reduce severity, frequency, or both, of respiratory distress syndrome, intracranial hemorrhage, necrotizing enterocolitis and death in neonates ( 7 ).…”
Section: Introductionmentioning
confidence: 99%